Optimizing squat technique - Comfort, P.; Kasim, P. (Strength and Conditioning Journal, 2007)
There are many variations of the squat technique, including stance width, foot positioning, and squat depth. However, research indicates that the optimal squat technique is a wide stance (shoulder width) with natural foot positioning, unrestricted movement of the knees, and full depth while the lordotic curve of the lumbar spine is maintained with a forward or upward gaze.